The association of serum 25‐OH vitamin D with atopy, asthma, and lung function in a prospective study of Danish adults. Issue 1 (January 2015) - Thuesen, B. H.; Skaaby, T.; Husemoen, L. L. N.; Fenger, M.; Jørgensen, T.; Linneberg, A.
Summary Background Besides the important skeletal functions, it has been suggested that vitamin D is involved in the pathogenesis of allergy and asthma and related to lung function. However, previous studies are inconclusive. Objective The purpose of this study was to investigate associations of serum levels of 25‐hydroxy vitamin D (25(OH)D) with atopy, asthma, and lung function in a prospective study of Danish adults. Methods This study included 4999 adults aged 30–60 years in 1999–2001. Three thousand and thirty‐two of those included at baseline also participated at a follow‐up examination 5 years later, and 3727 answered a 10‐year follow‐up questionnaire. Serum levels of (25(OH)D) were measured by high‐performance liquid chromatography (HPLC) at baseline. No information on use of vitamin D supplements was available. Specific IgE against four common antigens was measured. Information about doctor‐diagnosed asthma was obtained from questionnaires, and lung function (FEV1 and forced vital capacity) was measured by spirometry. Results We found no significant associations of 25(OH)D with atopy and doctor‐diagnosed asthma. However, we found that low levels of 25(OH)D were associated with lower FEV1 percentage predicted (FEV1%pred) in the cross‐sectional analyses. The odds ratio (OR) of FEV1%pred < 80% among participants in the highest quartile of 25(OH)D compared with those in the lowest was 0.66 (95% confidence interval (CI): 0.49–0.74). In contrast, prospective analyses indicated an association between high levels of 25(OH)D at baseline and adverse changes in lung function. OR (95%CI) of incident FEV1%pred < 80% was 1.73 (1.06–2.82) in the highest quartile of 25(OH)D compared with the lowest. Conclusions and Clinical Relevance Our data indicates that 25(OH)D levels do not influence the development of asthma and allergy among adults. Further, the results did not consistently support that 25(OH)D levels associate with lung function. Randomized controlled trials are needed to further address this issue.